Agent Communication International Workshop on Agent Communication, AC 2004, New York, NY, July 19, 2004 - van Eijk, Rogier M.; Huget, Marc-Philippe; Dignum, Frank (Lecture Notes in Artificial Intelligence, 2005)
In this book, we present a collection of papers around the topic of agent com- nication. The communication between agents has been one of the major topics of research in multiagent systems. The current work can therefore build on a number of previous Workshops of which the proceedings have been published in earlier volumes in this series. The basis of this collection is formed by the accepted submissions of the Workshop on Agent Communication held in c- junction with the AAMAS Conference in July 2004 in New York. The workshop received 26 submissions of which 14 were selected for publication in this v- ume. Besides the high-quality workshop papers we noticed that many papers on agent communication found their way to the main conference. We decided therefore to invite a number of authors to revise and extend their papers from this conference and to combine them with the workshop papers. We believe that the current collection comprises a very good and quite complete overview of the state of the art in this area of research and gives a good indication of the topics that are of major interest at the moment. The papers can roughly be divided over the following ?ve themes: - social commitments - multiparty communication - content languages - dialogues and conversations - speech acts Although these themes are of course not mutually exclusive they indicate some main directions of research. We therefore have arranged the papers in the book according to the topics indicated above.